Patient Classification and Automatic Configuration of an Intelligent Wheelchair - Faria, Brigida Monica (2019)
The access to instruments that allow higher autonomy to people is increasing and the scientific community is giving special attention on designing and developing such systems. Intelligent Wheelchairs (IW) are an example of how the knowledge on robotics and artificial intelligence may be applied to this field. IWs can have different interfaces and multimodal interfaces enabling several inputs such as head movements, joystick, facial expressions and voice commands. This paper describes the foundations for creating a simple procedure for extracting user profiles, which can be used to adequately select the best IW command mode for each user. The methodology consists on an interactive wizard composed by a flexible set of simple tasks presented to the user, and a method for extracting and analyzing the user’s execution of those tasks. The results showed that it is possible to extract simple user profiles, using the proposed method.